Unidade de ensino como possibilidade para discutir conceitos de estequiometria - Silva, Gilles Bastos e (2024)
The difficulties of the teaching-learning process led to the emergence of methodologies that aid the process of understanding. In Chemistry, there is Stoichiometry, whose learning difficulties are associated with the three levels of description of matter: macroscopic (observational), submicroscopic (atomicmolecular) and representational (symbols, formulas and equations). Furthermore, the student must be able to relate the transitions between levels, and make use of mathematical calculations, in order to signify the relationships, often through abstract situations that create barriers to learning. Given this, the following question arises: Does the use of a Teaching Unit help in understanding the concepts that should be used to teach relationships in Stoichiometry? Thus, the aim, in general, is to develop a Teaching Unit to discuss concepts in Stoichiometry. Specifically, we seek to contextualize the subject and its importance, observe whether there was a contribution to the development of meanings in the students' cognitive structure after applying the Teaching Unit, and develop potentially significant activities on the content of Stoichiometry. In this way, the development of a didactic sequence elaborated through qualitative action research based on Ausubel's theory is justified, in order to identify how subjects construct and modify their meanings in different educational contexts, using methods such as questionnaires, observations, document analysis, among others. As for methodology, action research was carried out as it is a reflective, systematic, controlled and critical procedure, oriented towards solving situational and specific problems, always driven by the desire for change, transformation. As a result, an analysis of the difficulties of high school students at a public school in Fortaleza was obtained, culminating in the creation of a Teaching Unit to Discuss Concepts of Stoichiometry, in which activities were presented that aim to assist teachers in a better process teaching-learning approach for Stoichiometry content.